The temperature gradient in and around solar magnetic fluxtubes - Sheminova, V.A.; Rutten, R.J.; Rouppe van der Voort L.H.M. (Кинематика и физика небесных тел, 2005)
We use spectra covering the outer part of the extended wing of the solar Ca II K line observed at high angular resolution with the Swedish Vacuum Solar Telescope to test standard solar fluxtube models. The wings of the Ca II resonance lines are formed in LTE both with regard to excitation (source function) and to ionization (opacity) and, therefore, sample temperature stratifications in relatively straightforward fashion. We obtain best fits by combining steeper temperature gradients than those in the standard models for both the tube inside and the tube environment. Similarly steep gradients are also determined from a numerical magnetoconvection simulation by the late A. S. Gadun. It is found that the energy balance in the individual magnetic elements appears to be close to radiative equilibrium throughout the photosphere.